Controlling Human Upright Posture: Velocity Information Is More Accurate Than Position or Acceleration - Jeka, John; Kiemel, Tim; Creath, Robert; Horak, Fay; Peterka, Robert (Journal of neurophysiology, 2004)
1 Program in Neuroscience & Cognitive Science, 2 Departments of Kinesiology and 3 Biology, University of Maryland, College Park, Maryland 20742-2611; and 4 Neurological Sciences Institute, Oregon Health & Science University, Portland, Oregon 97239-3098 Submitted 13 October 2003; accepted in final form 5 May 2004 The problem of how the nervous system fuses sensory information from multiple modalities for upright stance control remains largely unsolved. It is well established that the visual, vestibular, and somatosensory modalities provide position and rate (e.g., velocity, acceleration) information for estimation of body dynamics. However, it is unknown whether any particular property dominates when multisensory information is fused. Our recent stochastic analysis of postural sway during quiet stance suggested that sensory input provides more accurate information about the body's velocity than its position or acceleration. Here we tested this prediction by degrading major sources of velocity information through removal/attenuation of sensory information from vision and proprioception. Experimental measures of postural sway were compared with model predictions to determine whether sway behavior was indicative of a deficit in velocity information rather than position or acceleration information. Subjects stood with eyes closed on a support surface that was 1 ) fixed, 2 ) foam, or 3 ) sway-referenced. Six measures characterizing the stochastic structure of postural sway behaved in a manner consistent with model predictions of degraded velocity information. Results were inconsistent with the effect of degrading only position or acceleration information. These findings support the hypothesis that velocity information is the most accurate form of sensory information used to stabilize posture during quiet stance. Our results are consistent with the assumption that changes in sway behavior resulting from commonly used experimental manipulations (e.g., foam, sway-referencing, eyes closed) are primarily attributed to loss of accurate velocity information. Address for reprint requests and othercorrespondence: J. Jeka, University of Maryland, College Park, MD 20742-2611(E-mail: jjekaatumd.edu ).